2019
DOI: 10.33585/cmy.71107
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the occurrence of fungi causing postharvest diseases of apples grown in organic and integrated production systems in orchards in the Czech Republic.

Abstract: During the years 2013-2015, the occurrence of fungi causing postharvest diseases of apples was evaluated in three apple orchards with integrated and organic production systems in the Czech Republic. The postharvest disease fungi were more frequently recorded in fruits from organically cultivated apple trees (average 29.97%) than those from integrated production (17.67%). This difference is statistically significant. Neofabraea, Penicillium, Alternaria and a sterile grey mycelium were the most frequently record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Genetic variation among cultivars (each cultivar usually corresponds to a single genotype in apple and other clonally propagated crops) is the basis for selection-mediated improvement, and the subsequent development of superior cultivars. Considerable variation among cultivars in their susceptibility to some of the most common storage rots has been reported from observations in orchards and storage rooms [ 3 , 19 , 21 , 40 , 43 , 70 ]. Still, levels of resistance cannot be properly quantified based only on natural infections, since the inocula may vary in both quantity and virulence.…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%
See 2 more Smart Citations
“…Genetic variation among cultivars (each cultivar usually corresponds to a single genotype in apple and other clonally propagated crops) is the basis for selection-mediated improvement, and the subsequent development of superior cultivars. Considerable variation among cultivars in their susceptibility to some of the most common storage rots has been reported from observations in orchards and storage rooms [ 3 , 19 , 21 , 40 , 43 , 70 ]. Still, levels of resistance cannot be properly quantified based only on natural infections, since the inocula may vary in both quantity and virulence.…”
Section: Quantification Of Storage Rot Damagementioning
confidence: 99%
“…Tul., Nectria galligena Bres. Nectria rot (apple canker or European canker on trees) [20,50] Penicillium expansum Link Blue mould [3,5,6,12,15,21,25,[31][32][33]38,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66] Phacidiopycnis spp., e.g., P. malorum Potebnia and P. washingtonensis Xiao & J.D. Rogers…”
Section: Fungi That Cause Storage Rotmentioning
confidence: 99%
See 1 more Smart Citation
“…The least affected cultivar was 'Ligol' (0.2-1.3%). Blazek et al [2006], Ivic et al [2012] and Novotny et al [2019] found in their studies that infestation of apples by Monilinia fructigena Aderh. et Ruhl.…”
Section: Discussionmentioning
confidence: 99%
“…[2011] in Greece demonstrated that B. cinerea is one of the most common (23.6%) pathogens that cause rotting in stored apples. Ivic et al [2012] and Novotny et al [2019] report that B. cinerea infects apples in the ranges of 0.2-0.53% and 0.15-0.35%, respec-tively. This pathogen belongs to the group of fungi that infect fruit through skin defects (wounds).…”
Section: Discussionmentioning
confidence: 99%